Análisis del diseño estructural para un parqueo vehicular multinivel en la Universidad Laica Vicente Rocafuerte de Guayaquil - Álvarez Lavayen, Samuel Isaac (2025)
This structural design project for a multi-level parking facility at the Universidad Laica Vicente Rocafuerte de Guayaquil aims to address the growing demand for parking on campus by optimizing the use of available space without affecting vehicular circulation or accessibility. The design focuses on the creation of a multi-story structure capable of accommodating a greater number of vehicles, thereby improving mobility within the university. Additionally, key factors such as safety, ease of access, and reduced waiting times for users are taken into consideration. The proposed structural solution consists of a steel-framed building with moment-resisting frames, complemented by diagonal cross-bracing in certain bays to efficiently control lateral drift. The building will include one basement level and six upper floors, providing a total capacity of 108 parking spaces, distributed evenly at 18 spaces per level. The design also incorporates an elevator and a metal staircase to ensure comfortable and safe movement for users.........